Stock-flow adjustment - only a residual value? Evidence from European Union countries - Monika Banaszewska (e-Finanse: Financial Internet Quarterly, 2019)
The aim of the article is to investigate the fiscal determinants of stock-flow adjustment (SFA). Previous literature suggests that SFA may be used strategically to reduce budget deficit and public debt. As such, SFA impairs fiscal transparency and may endanger fiscal sustainability. Therefore, special attention should be paid by economists and policymakers. The study pertains to the European Union countries in the years 2005-2016. The empirical analysis supports the hypothesis that SFA is inversely related to public debt, whereas the inverse relationship between budget balance and SFA is not confirmed. The article contains additional analyses for selected components of SFA as well as narrower time and space coverage.
Keywords: E62; H62; H63; 330; public debt; budget deficit; panel data analysis